"R" is for ricochet : [compact disc, unabridged] : a Kinsey Millhone mystery - Grafton, Sue (Grafton, Sue. Kinsey Millhone mysteries., 2004)
No sooner is Reba Lafferty, a child of privilege, released from prison for embezzlement, when someone from her past pays her a visit.